Leveraging FinTech-Driven Financial Inclusion and ESG Integration to Advance Affordable and Clean Energy Access - Khasawneh, Ohoud; Alzghoul, Amro (International Journal of Energy Economics and Policy, 2026)
The paper discusses how digital financial inclusion powered by financial technology and incorporation of environmental, social, and governance principles into finance can hasten the achievement of Sustainable Development Goal 7. We provide a systematic literature review, which relies on peer-reviewed literature in energy economics, sustainable finance, and development literature. Our search and screening strategy is informed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The analysis shows that financial inclusion, which is promoted by FinTech (e.g. mobile banking, digital lending, and crowdfunding) has increased access to energy (e.g. pay-as-you-go solar, microfinance to clean cooking) especially by underserved communities in Asia, the Middle East and Africa. At the same time, the ESG consideration in financial decision-making is directing investments to renewable energy and energy efficiency initiatives. We discover that digital platforms and blockchain-based tools increase the levels of ESG data transparency and integrity, and strengthen the confidence of investors in green energy ventures. Nonetheless, it is also evidenced that financial inclusion should be accompanied with the introduction of clean energy to prevent the need to emit more carbon into the air through the consumption of additional energy. Our research gaps are household-level behavior, ESG adoption in developing markets and FinTech governance. Government and industry policies like subsidizing energy delivery through digital payments and requiring ESG reporting of FinTech companies will have the effect of making digital finance and sustainability agendas mutually reinforcing. All these points highlight the cross-cutting enabling nature of FinTech in sustainable energy shifts and the need to collaborate interdisciplinarily to utilize digital finance to achieve global clean energy targets.